THE INFLUENCE OF CUSTOMER ORIENTATION ON MSME PERFORMANCE, WITH SOCIAL MEDIA ADOPTION AS A MODERATION VARIABLE (STUDY ON MSME CULINARY SECTOR IN PEKANBARU CITY) - Fauzi, M Fakhrur Rozi; Efnita, Yul (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The aim of this research is to examine the influence of customer orientationon MSME performance mediated by social media adoption. This research was conducted with a research sample of 115 respondents in the culinary sector of MSMEs in Pekanbaru City. This research adopts a quantitative approach with a descriptive point of view. Sampling is usually done randomly. Structural Equation Modeling software based on Partial Least Square (SEM-PLS). The results of this research show that customer orientation and social media adoption have a direct relationship with the performance of MSMEs. In an indirect relationship, customer orientation influences MSME performance through social media adoption. Keywords: Customer orientation, performance, social media adoption